Nicsp 17 propiedad planta y equipo: tratamiento contable en el sector público no financiero. - Cordova Gonzalez, Angie Belen (Universidad Técnica de Machala, 2022)
The present research work is oriented towards building the accounting records and the due budgetary execution focused on long-term assets belonging to the public sector, whose goal is to know how the financial and budgetary accounting treatment of the asset category is carried out, taking into account account the International Accounting Standard directed to the public sector N ° 17 (NICSP 17) where in Ecuador it came into force from the year 2018 through a convergence plan, in order to develop public administrative processes with the greatest transparency and legitimacy in each process, facilitating in turn the understanding and interpretation of this regulation. The objective of this research is to identify the appropriate accounting treatment for the adoption of IPSAS 17 property, plant and equipment in the acquisition of medical equipment applied to the non-financial public sector. Whose methodological journey involves descriptive analysis through the use of bibliographic reviews, books, academic articles, accounting standards and other texts considered essential for the theoretical basis for this work. In addition, a practical case is presented where the accounting records of an entity belonging to the public sector are disclosed where an asset of property, plant and equipment is acquired, where the accounting information is transparent for its subsequent analysis and for its respective decision making. in public institutions.
El presente trabajo de investigación se orienta en construir los registros contables y la debida ejecución presupuestaria enfocado en los bienes de larga duración perteneciente al sector público, cuya meta es conocer cómo se realiza el tratamiento contable financiero y presupuestario del rubro de los activos, teniendo en cuenta la Norma Internacional de Contabilidad dirigido al sector público N°17 (NICSP 17) donde en el Ecuador entro en vigencia a partir del año 2018 a través de un plan de convergencia, con el fin de desarrollar procesos administrativos públicos con la mayor transparencia y legitimidad en cada proceso, facilitando a su vez la comprensión e interpretación de esta normativa. El objetivo de esta investigación es identificar el tratamiento contable adecuado para la adopción de la NICSP 17 propiedad planta y equipo en la adquisición de equipos médicos aplicado al sector público no financiero. Cuyo recorrido metodológico implica al análisis descriptivo mediante el uso de revisiones bibliográficas, libros, artículos académicos, normas contables y otros textos considerados esenciales para base teórica para este trabajo. Además, se plantea un caso práctico donde se da a conocer los registros contables de una entidad perteneciente al sector publico donde se adquiere un activo de propiedad, planta y equipo, donde la información contable sea transparente para su posterior análisis y para su respectiva toma de decisiones en las instituciones públicas.
Keywords: CONTABILIDAD GUBERNAMENTAL; NICSP 17; ROPIEDAD PLANTA Y EQUIPO; SECTOR PÚBLICO NO FINANCIERO